IL-1β increases asporin expression via the NF-κB p65 pathway in nucleus pulposus cells during intervertebral disc degeneration - Shengjie Wang (Nature Portfolio, 2017)
Abstract Disc degeneration (DD) is a multifaceted chronic process that alters the structure and function of intervertebral discs. The pathophysiology of degeneration is not completely understood, but the consensus is that changes in genes encoding extracellular matrix (ECM) proteins in the disc are the leading factors contributing to DD. Asporin is an ECM protein that has been shown to be increased in degenerated intervertebral discs, but little is known about how asporin is regulated during DD. In exploring the intricate mechanism, we confirmed that asporin was abundantly increased in patients’ degenerated nucleus pulposus. Consistently, the increased asporin expression with degeneration was also proved by rabbit intervertebral disc degeneration (IDD) model. Mechanistically, IL-1β upregulated asporin expression by activating the p65 pathway in human nucleus pulposus cells. Furthermore, p65 mediated asporin expression by binding to −41/−31 bp on asporin promoter. Functionally, asporin was the intermediator of IL-1β-inhibited aggrecan and collagen Π expression and played a negative role in TGF-β-induced aggrecan and collagen Π formation in human nucleus pulposus cells. Therefore, identifying asporin as a negative regulator of aggrecan and collagen Π and elucidating its induction mechanisms in human nucleus pulposus cells provides new insight for asporin induction during IDD.